Religiöse Spuren im Alltag - Matthias Werner (Warszawskie Studia Teologiczne)
Acronyms, songs, advertisements, movies, television series, comic strips, memes or even sports news: Traces of Christian symbols, sayings, or references can be found in numerous places and contexts. But most children and adolescents exposed to religious education in German schools, only know these contemporary references without being aware of their origins. So one of the most challenging tasks in religious education is enabling learners to decode those references and adaptations. Being able to decode the occurring transformations of religion within these daily life phenomena is the prerequisite for being able to make an informed decision about the underlying concepts and religious ideas.  This article provides an example of how to alternatively address the quite abstract teaching of dyophysitism by using snippets of the famous animated sitcom „The Simpsons“.